Slums: Affects on environment - Agrawal, Vandana (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Urban living is the keystone of modern human ecology. Cities have increased and expanded rapidly worldwide over the past centuries. Cities are sources of employment and education, and they are the engines for economic growth. However, they are also sources of poverty, inequality, and health hazards from the environment. Environmental decay in a city is essentially caused by rapid urbanization and the mismatch in the provision and maintenance of housing and infrastructure. These include exposure to lead, air pollution, traffic hazards, and the "urban heat island" amplification of heat waves. As the number of urban consumers and their material expectations rise and as the use of fossil fuels increases, cities contribute to the large-scale pressures on the biosphere including climate change. In this paper, environmental problems of slum and informal settlements in India, will be introduced and analysed. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>